A 16kV distribution network reconfiguration by using evolutionaring programming for loss minimizing - Sulaima, Mohamad Fani; Shidan, Murnie Shakilla; Mohd Dahalan, Wardiah; Mokhlis, Hazlie; Baharom, Mohamad Faizal; Jaafar, Hazriq Izzuan (Research India Publications, 2014)
In the worldwide trend toward restructuring the electricity network; there are a lot of problems. Where with the increasing of electricity demand, intelligence algorithm is one of the optimization search engine that may help in minimizing the power losses in the power distribution network. This paper presents a method of 16kV Distribution Network Reconfiguration (DNR) by using Evolutionary Programming (EP). The main objectives of this study are to minimize the power losses and improve the voltage profile while analyzing the consistency and computing time effectively. The performance of the Evolutionary Programming method will be investigated and the impact to the 16kV distribution network will be analyzed. The real result will be compared with the conventional initial network and other optimization technique which is Genetic Algorithm (GA). The results of this study is hoped to help the power system engineers in Malaysia in order to solve the losses problem in the plant at the same time increasing the efficiency of the real 16-bus distribution system.